Using Parallel Corpora for Translation Activities in L2 Medical English Undergraduate Teaching, with Specific Reference to Italian Sports Sciences Courses - Barbara Cappuzzo (European Scientific Journal, ESJ, 2021)
English is the international language of science and, as such, it is also the international language of medicine. L2 English undergraduates do not generally have particular difficulties in translating from English into their mother tongue; by contrast, they do not perform very well when asked to translate into English. The aim of this report is to show the results of a study obtained by using parallel corpora in scientific English classes in the Italian sports sciences study course of the University of Palermo. The students were provided with a corpus of English texts taken from a well-known medical text with pedagogical purposes, and their corresponding Italian translations, which were carried out by medical doctors. The students were asked to compare the two languages and were guided to identify major differences in lexical choices, syntactical structures, textual features, and units of meaning. They were then invited to translate relevant parts of texts from English into Italian mainly on the basis of what they remembered of the Italian version, and afterwards they were asked to perform back-translation activities into English following the same procedure. They gradually became familiar with the discourse patterns of medical English and medical Italian, and showed a better control in the correct use of scientific vocabulary. Most importantly, they developed awareness of the fact that specialized translation is an activity that demands rigorous compliance with the rules and conventions of a given linguacultural domain.